Pengembangan Perangkat Pembelajaran Berbasis Smartphone dengan Tema Budaya Hombo Batu Pada Hukum Newton dan Gerak Parabola - M Reza Dwi Saputra; Faruq Fahroky; Jamiatul Khairunnisa Putri (JURNAL PENDIDIKAN DAN SAINS, 2022)
Abstract— This study aims to develop smartphone-based learning tools with the theme of Hombo Batu culture, Nias in the form of syllabus, lesson plans (RPP), student discussion sheets, and knowledge assessment instruments. The development of this learning tool uses the Four-D Model (Define, Design, Develop and Disseminate). The definition is carried out by studying literature, observing learning at school, interviewing Physics teachers and students regarding smartphone-based learning devices and cultural integration in learning. Learning tools are designed according to the 2013 curriculum, substitution of smartphone learning media, and integration of hombo batu culture in the material. Learning devices are developed based on the learning media used in the form of Android smartphones with learning media applications that have been developed and installed on students' smartphones. Dissemination is carried out by distributing products to schools in Bengkulu City. The learning device trials were carried out in two stages: limited testing (small group) and field testing (one class) with one pretest-posttest design group. From the results of the analysis and discussion, it can be concluded that the score of the learning device based on Physics Mobile Learning with the theme of Hombo Batu culture is categorized as very good after being assessed by experts, teachers and colleagues. This learning device gets Aiken V on Syllabus 0.95; RPP of 0.94 student discussion sheets of 0.93 and test instruments of 0.85 with a pretest score of 28.96 and a posttest score of 76.10. The validity as seen from the Aiken V score (greater than the Aiken V table value) concluded that the learning device based on physics mobile learning with the theme of Hombo batu culture is valid and suitable for use in learning Physics on Newton's Laws and Parabolic Motion.